COMPUTATIONAL STUDY ON INTERACTION OF HALOACID DEHALOGENASE FROM BACILLUS CEREUS INDB1 WITH 2-CHLOROALKANOIC ACID SUBSTRATES - Saepulloh
Haloacid dehalogenase has been widely studied because of its potential application in bioremediation and agrochemical industries. The haloacid dehalogenase gene from Bacillus cereus IndB1 (bcfd1) has been isolated, heterologously expressed in E. coli BL21/pET-30a(+), and its activity towards monochloroacetic acid has been extensively studied. However, the structure, stereoselectivity, substrate range, and interactions of Bcfd1 with haloacids have not been studied. In this research, a computational study was conducted to predict the tertiary structure of Bcfd1 and to study its interaction with nine different 2-chloroalkanoic acids. The study would include Bcfd1 stereoselectivity and the effect of carbon skeleton length in the substrates. The tertiary structure prediction show that Bcfd1 has two domains, main and cap domain. The main domain consists of seven ?-sheets linked by six ?-helices and four 310-helices forming a Rosmann fold, similar with main domain of all other L-haloacid dehalogenases. On the other hand, the cap domain consists of five ?- sheets connected by five ?-helices which found to be different with other L-haloacid dehalogenase. The results of molecular docking using nine 2-chloroalkanoic acid substrates with up to six carbon atoms showed that all substrates could be bound to the active site of Bcfd1 without any significant difference in docking scores between L-2- and D-2-chloroalkanoic acids. However, molecular dynamics simulations showed that complexes of Bcfd1-monochloroacetic acid and Bcfd1- D,L-2-chloropropanoic acid were more stable than other complexes, indicated by lower binding free energies compare to other substrates which have more carbon atoms. The results of alanine scanning showed that the residues of Met1, Asp2, Ser34, Lys204, Asp231, and Met234 contributed to the binding free energy. This study shows that Bcfd1 is a member of Haloacid Dehalogenase (HAD) superfamily which has higher affinity towards monochloroacetic acid and D,L-2- chloropropionic acid than other 2-chloroalkanoic acids.